Global estimates on the number of people blind or visually impaired by age-related macular degeneration: a meta-analysis from 2000 to 2020 - Furtado, João M.; Jonas, Jost B. (Eye, 2024)
We aimed to update estimates of global vision loss due to age-related macular degeneration (AMD).
Online veröffentlicht: 4. Juli 2024
Mitglieder der Vision Loss Expert Group of the Global Burden of Disease Study:João M. Furtado, Jost B. Jonas, Ian Tapply, Arthur G. Fernandes, Maria Vittoria Cicinelli, Alessandro Arrigo, Nicolas Leveziel, Serge Resnikoff, Hugh R. Taylor, Tabassom Sedighi, Seth Flaxman, Maurizio Battaglia Parodi, Mukkharram M. Bikbov, Tasanee Braithwaite, Alain Bron, Ching-Yu Cheng, Nathan Congdon, Monte A. Del Monte, Joshua R. Ehrlich, Tim Fricke, David Friedman, Gus Gazzard, M. Elizabeth Hartnett, Rim Kahloun, John H. Kempen, Moncef Khairallah, Rohit C. Khanna, Judy E. Kim, Van Charles Lansingh, Janet Leasher, Kovin S. Naidoo, Vinay Nangia, Michal Nowak, Konrad Pesudovs, Tunde Peto, Pradeep Ramulu, Fotis Topouzis, Mitiadis Tsilimbaris, Ya Xing Wang, Ningli Wang and Rupert R.A. Bourne
Mitglieder der The GBD 2019 Blindness and Vision Impairment Collaborators: João M. Furtado, Jost B. Jonas, Arthur G. Fernandes, Maria Vittoria Cicinelli, Nicolas Leveziel, Paul Svitil Briant, Theo Vos, Serge Resnikoff, Florian Fischer, Yohannes Habtegiorgis Abate, Mohammad Abdollahi, Tadele Girum Girum Adal, Isaac Yeboah Addo, Kishor Adhikari, Prerna Agarwal, Antonella Agodi, Williams Agyemang-Duah, Aqeel Ahmad, Hamid Ahmadieh, Hooman Ahmadzadeh, Fares Alahdab, Ahmad Samir Alfaar, Robert Kaba Alhassan, Syed Shujait Shujait Ali, Louay Almidani, Sofia Androudi, Abhishek Anil, Anayochukwu Edward Anyasodor, Jalal Arabloo, Mubarek Yesse Ashemo, Seyyed Shamsadin Athari, Desta Debalkie Atnafu, Alok Atreya, Melese Kitu Ayalew, Yared Asmare Aynalem, Zewdu Bishaw Aynalem, Ahmed Y. Azzam, Sara Bagherieh, Ruhai Bai, Martina Barchitta, Mainak Bardhan, Till Winfried Bärnighausen, Nebiyou Simegnew Bayileyegn, Fatemeh Bazvand, Ahmet Begde, Babak Behnam, Akshaya Srikanth Bhagavathula, Sonu Bhaskar, Gurjit Kaur Bhatti, Jasvinder Singh Bhatti, Bagas Suryo Bintoro, Marina G. Birck, Tasanee Braithwaite, Katrin Burkart, Yasser Bustanji, Florentino L. Caetano dos Santos, Vera L.A. Carneiro, Muthia Cenderadewi, Vijay Kumar Chattu, Dinh-Toi Chu, Kaleb Coberly, Natália Cruz-Martins, Omid Dadras, Xiaochen Dai, Ana Maria Dascalu, Mohsen Dashti, Anna Dastiridou, Maedeh Dastmardi, Xinlei Deng, Nikolaos Dervenis, Vinoth Gnana Chellaiyan Devanbu, Mengistie Diress, Shirin Djalalinia, Joshua R. Ehrlich, Michael Ekholuenetale, Temitope Cyrus Ekundayo, Iman El Sayed, Muhammed Elhadi, Mehdi Emamverdi, Ambaw Abebaw Emrie, Adeniyi Francis Fagbamigbe, Ayesha Fahim, Umar Farooq, Hossein Farrokhpour [und viele Weitere]
Gesehen am 18.02.2025